Cultural Cooking as Parenting Pedagogy: Strengthening Father–Child Attachment in Early Childhood Education - Anggraini , Vivi; Dwi Febriani, Rahmi; Anggraini, Ezi; Priyanto, Adi; Novela, Tia; Yulsyofriend, Yulsyofriend; Septia Ochi Wahyuni, Dwi (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study explores the effectiveness of fun cooking activities using Minangkabau traditional food as a culture-based pedagogical strategy to strengthen father–child attachment in early childhood education settings. The research aims to demonstrate how local cultural practices can serve as meaningful tools for fostering emotional connection and parental engagement.Design/methods/approach – A quantitative pre-experimental design with a one-group pretest–posttest approach was employed to measure changes in attachment levels before and after the intervention. The study utilized a structured questionnaire encompassing four key indicators of attachment: frequency of interaction, emotional warmth, involvement in activity, and father–child communication. Data were collected through action-based activities, and the degree of improvement was analyzed using the N-gain formula to assess effectiveness.Findings – The findings revealed a significant increase in all four indicators of father–child attachment after participating in the fun cooking sessions. The most substantial improvements occurred in emotional warmth and involvement in the activity, suggesting that shared cooking experiences offer a highly interactive and emotionally rewarding context for strengthening familial bonds. These outcomes indicate that collaborative culinary activities not only promote affection and cooperation but also enhance communication and active participation between fathers and their young children.Research implications/limitations – The findings are context-specific to the Minangkabau community, which may limit their generalizability to other cultural settings. Future studies with larger samples and comparative designs are recommended.Practical implications – The study provides insights for educators, family practitioners, and policymakers on how local culture-based activities can be integrated into parenting programs to encourage father engagement. It underscores the significance of embedding local wisdom in designing family-centered educational practices. Originality/value – This research offers a novel perspective on fatherhood by positioning cultural cooking as a pedagogical tool to enhance paternal attachment. It expands the literature on father engagement in early childhood education and demonstrates how cultural traditions can be leveraged for sustainable parenting and educational practices.Paper type Research paper